The Impact of Economic Policy Uncertainty on Government Bond Pricing - Nanayakkara Vidhana Arachchige, Nimna (2024)
This study examines the impact of economic policy uncertainty (EPU), encompassing fiscal policy uncertainty, monetary policy uncertainty, trade policy uncertainty, and inflation uncertainty, on government bond prices and bond market behaviour. Through empirical analysis, the study identifies significant positive relationships among the variables elucidating the intricate dynamics shaping bond pricing amidst policy uncertainty. Government bond prices are crucial in determining economic stability and financial system stability. Therefore, the topic was selected to analyse how policy uncertainty influences government bond prices. Here the study focuses on the U.S. bond market, particularly with 10-year yield.